Timely care: Rhythms of bureaucracy and everyday life in cases involving youths with complex needs. (November 2019) - Andersen, Ditte; Bengtsson, Tea Torbenfeldt
Through a conceptualization of timely care defined as the right care at the right time, this article analyzes the challenges involved in synchronizing the needs of vulnerable youth with the care provided through the welfare state bureaucracy. While the process of timing care provision with fluctuating human needs is a major challenge for any welfare state bureaucracy, the issue of time has yet to be integrated systematically into research on care provision. In particular, the subjective time dimensions of care remain understudied. To help address this gap, we introduce Henri Lefebvre's work on rhythms to develop a deeper theoretical understanding of how the rhythms of everyday life and the bureaucracy face a continuous risk of falling "out of sync." Empirically, we draw on two studies of care provision in Denmark: one study focusing on youths with complex needs and the other focusing on welfare state professionals' provision of care. The analysis demonstrates various ways in which the professional rhythms of bureaucracy and the everyday lives of youth can be out of sync and how that can be reflected in different youth experiences such as neglect and clientization. Conversely, we demonstrate how care provided "in sync" with a youth's perceived needs is experienced as timely. Based on this, we argue that provision of timely care is possible in welfare state bureaucracies given sensitivity toward the subjective time dimensions.